Kritik Sosial dalam Film Dokumenter Ruang Gelap di Balik Kemegahan Stadion Internasional Jakarta - M. Rohid; Ahmad Harun Yahya; Eni Murdiati (CV. Ulil Albab Corp, 2023)
The purpose of this study is to find out the social criticism represented through a documentary film entitled The Dark Room Behind the Splendor of the Jakarta International Stadium from the Assumption YouTube channel. Seen from Representment, Object and Interpretation. The Assumption YouTube channel on February 11 2022 uploaded a documentary video that discusses life around the Jakarta International Stadium location which makes them sometimes have to leave their place of residence. This is a qualitative study using Charles Sanders Peirce's semiotic analysis. The data source used by the researcher, namely the primary data source, is a video uploaded on the Assumption YouTube channel with the title The Dark Room Behind the Splendor of the Jakarta International Stadium. Other sources are secondary data sources including internet news, journals and previous theses, as well as books related to research. Observation and documentation are data collection strategies used in data analysis. From the results of research to find representations of social criticism in the documentary film The Dark Room Behind the Splendor of the Jakarta International Stadium, researchers have concluded that this representation can be seen from three points, namely the representamen, objects and interpretations represented from the dialogue monologues Ayong, Kasdiyah and Basadan as well as from taking pictures.